Uma abordagem para promover o alinhamento entre a estratégia de negócio e a tecnologia de informação - Oliveira, Karlos Thadeu Matias Vital de (2009)
Currently with the increase in complexity in doing business, organizations are seeking information systems that help to quickly respond to new demands in the processes of production of products and services. An information system is no longer just a support tool and has become an integral part of doing business. However, in spite of significant technological evolution in recent years, information systems that support business do not respond efficiently to the constant alterations that occur in many organizations. One of the main problems faced by information systems currently is the lack of strategic alignment between business strategy and information technology. The concept of strategic alignment can be defined as a way between business strategies and objectives and the strategies, objectives and functions of information technology in such as way as to contribute to the increase in competitivity of the organization over time. Strategic alignment together with strategic planning are important management instruments. Approaches for operationalizing this alignment are being developed currently but are still in their initial stages due to the fact that it is a relatively new concept in the literature. Another point that needs to be taken into consideration during the strategic alignment is the question of trackability between the business elements and IT. Trackability (Tracking) is necessary for example when one wishes to know exactly which goal defined in the business strategy was left out or not accepted due to a modification made in the IT strategy. Very few proposals present concrete ways supported by software systems in order to obtain strategic alignement while taking into consideration this trackability. Therefore the objective of this work is to propose the creation of a strategic alignment process supported by a software system which is capable of permitting trackability between the organizational objectives and the business processes based on formalization standards defined through a model oriented approach